1999
DOI: 10.1152/jn.1999.81.2.954
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Input Induces Three Firing Patterns in Neurons of the Superficial Superior Colliculus of Neonatal Rats

Abstract: By using an in vitro isolated brain stem preparation, we recorded extracellular responses to electrical stimulation of the optic tract (OT) from 71 neurons in the superficial superior colliculus (SC) of neonatal rats (P1-13). At postnatal day 1 (P1), all tested neurons (n = 10) already received excitatory input from the retina. Sixty-nine (97%) superficial SC neurons of neonatal rats showed three response patterns to OT stimulation, which depended on stimulus intensity. A weak stimulus evoked only one spike th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…However, the neurons and neural systems of these animals are functional under low perfusion rates and at low temperatures, unlike mammalian neural systems. Despite the experimental challenges associated with studying mammalian neurons, ex vivo methods continue to be developed to study mammalian sensory processing across brain regions and in intact CNS structures (Llinás and Mühlethaler, 1988; Mühlethaler et al, 1993; Lo and Mize, 1999; Ritter et al, 2000; Woodbury et al, 2001). Studying the AOS in vivo and ex vivo is particularly challenging due to the relative inaccessibility of the VNO and the long and delicate projections between the VNO and AOB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neurons and neural systems of these animals are functional under low perfusion rates and at low temperatures, unlike mammalian neural systems. Despite the experimental challenges associated with studying mammalian neurons, ex vivo methods continue to be developed to study mammalian sensory processing across brain regions and in intact CNS structures (Llinás and Mühlethaler, 1988; Mühlethaler et al, 1993; Lo and Mize, 1999; Ritter et al, 2000; Woodbury et al, 2001). Studying the AOS in vivo and ex vivo is particularly challenging due to the relative inaccessibility of the VNO and the long and delicate projections between the VNO and AOB.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Jena et al (1997), PTP1C is associated with synaptic vesicles and interacts directly with the vesicular protein synaptophysin, which suggests an involvement of PTP1C in synaptic transmission. Indeed, the expression profile of PTP1C in the superior colliculus correlates well with synaptogenesis, which starts approximately at P1 (Lo and Mize 1999). Furthermore, synaptophysin is up-regulated during neuronal development and maturation (Becher et al 1999a, b).…”
Section: Discussionmentioning
confidence: 99%
“…This is because physiological studies have shown the neural spikes are stochastic events. The spike trains are triggered short bursts of equal-amplitude spikes [15], [16]. As the stimuli repeated for simulaiton, the spike clusters are triggerred periodically.…”
Section: The Input Spike Train Generatingmentioning
confidence: 99%